Fiscal reforms and the fiscal effects of aid in Uganda - Bwire, Thomas; Morrissey, Oliver; Lloyd, Tim (Taylor & Francis, 2017)
Uganda implemented public expenditure and revenue management reforms from the early 1990s with specific aims of improving budget planning and aligning aid with fiscal priorities. The dynamic relationship between aid and domestic fiscal aggregates is analysed using a Cointegrated Vector Autoregressive model with annual data for 1972-2008 and quarterly data for 1997-2014. Aid has been a significant element of long-run fiscal equilibrium, associated with increased tax effort and public spending and reduced domestic borrowing. Fiscal reforms have improved aid and expenditure management, contributing to improved fiscal performance in Uganda, with lessons for other African countries.